# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime \prime \prime \prime }+y^{\prime \prime } = \sec \left (t \right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y^{\prime } = \sec \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+y^{\prime \prime } = \cos \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+y^{\prime \prime } = t
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-7 y^{\prime }+10 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+7 y^{\prime }+10 y = 0
\] |
✓ |
✓ |
|
\[
{}6 y^{\prime \prime }+5 y^{\prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-10 y^{\prime }+34 y = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime }-5 y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}15 y^{\prime \prime }-11 y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}20 y^{\prime \prime }+y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}12 y^{\prime \prime }+8 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime \prime }+3 y^{\prime \prime }+y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}9 y^{\prime \prime \prime }+36 y^{\prime \prime }+40 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}9 y^{\prime \prime \prime }+12 y^{\prime \prime }+13 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }-8 y = -t
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+5 y^{\prime } = 5 t^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime } = -3 \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+5 y = 3 \sin \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-9 y = \frac {1}{1+{\mathrm e}^{3 t}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime } = \frac {1}{{\mathrm e}^{2 t}+1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime }+2 y = -4 \,{\mathrm e}^{-2 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }+13 y = 3 \,{\mathrm e}^{-2 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+9 y^{\prime }+20 y = -2 t \,{\mathrm e}^{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+7 y^{\prime }+12 y = 3 t^{2} {\mathrm e}^{-4 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+3 y^{\prime \prime }-9 y^{\prime }+5 y = {\mathrm e}^{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-12 y^{\prime }-16 y = {\mathrm e}^{4 t}-{\mathrm e}^{-2 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+6 y^{\prime \prime \prime }+18 y^{\prime \prime }+30 y^{\prime }+25 y = {\mathrm e}^{-t} \cos \left (2 t \right )+{\mathrm e}^{-2 t} \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+4 y^{\prime \prime \prime }+14 y^{\prime \prime }+20 y^{\prime }+25 y = t^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+5 y^{\prime }+6 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+10 y^{\prime }+16 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+16 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+25 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y = t
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime }-4 y = {\mathrm e}^{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+9 y = \sin \left (3 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \cos \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = \tan \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \csc \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-8 y^{\prime }+16 y = \frac {{\mathrm e}^{4 t}}{t^{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-8 y^{\prime }+16 y = \frac {{\mathrm e}^{4 t}}{t^{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+y = {\mathrm e}^{t} \ln \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+y = {\mathrm e}^{t} \ln \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{\prime \prime }+9 x = 0
\] |
✓ |
✓ |
|
\[
{}9 x^{\prime \prime }+4 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+64 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+100 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+16 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+256 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+9 x = 0
\] |
✓ |
✓ |
|
\[
{}10 x^{\prime \prime }+\frac {x}{10} = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x^{\prime }+3 x = 0
\] |
✓ |
✓ |
|
\[
{}\frac {x^{\prime \prime }}{32}+2 x^{\prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}\frac {x^{\prime \prime }}{4}+2 x^{\prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{\prime \prime }+2 x^{\prime }+8 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x^{\prime }+13 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x^{\prime }+20 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x = \left \{\begin {array}{cc} 1 & 0\le t <\pi \\ 0 & \pi \le t \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x = \left \{\begin {array}{cc} \cos \left (t \right ) & 0\le t <\pi \\ 0 & \pi \le t \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x = \left \{\begin {array}{cc} t & 0\le t <1 \\ 2-t & 1\le t <2 \\ 0 & 2\le t \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+4 x^{\prime }+13 x = \left \{\begin {array}{cc} 1 & 0\le t <\pi \\ 1-t & \pi \le t <2 \pi \\ 0 & 2 \pi \le t \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x = \cos \left (t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x = \cos \left (t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x = \cos \left (\frac {9 t}{10}\right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x = \cos \left (\frac {7 t}{10}\right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+\frac {x^{\prime }}{10}+x = 3 \cos \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }-3 x^{\prime }+4 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+6 x^{\prime }+9 x = 0
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+16 x = t \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+x = {\mathrm e}^{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = 2 \cos \left (x \right )+2 \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime }+2 y = 2
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime } = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime } = x +\cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = x \,{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = 2 x \ln \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+2 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}3 y^{\prime \prime }-2 y^{\prime }-8 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-3 y^{\prime \prime }+3 y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+6 y^{\prime \prime }+11 y^{\prime }+6 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\left (6\right )}+2 y^{\left (5\right )}+y^{\prime \prime \prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }-8 y^{\prime }+5 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }-8 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+4 y^{\prime \prime \prime }+10 y^{\prime \prime }+12 y^{\prime }+5 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime \prime }+2 y^{\prime \prime \prime }+4 y^{\prime \prime }-2 y^{\prime }-5 y = 0
\] |
✓ |
✓ |
|